Unsettled screens: The Cinema of Latin America - Traverso, Antonio (Open Humanities Press, 2005)
It is because of the inherently paradoxical character of life in the vast and heterogenous region known as Latin America that the category "Latin American cinema" always requires to be rendered problematical. In fact, the phrase "Latin American cinema" does not mean the same, nor does it necessarily have meaning at all, to filmmakers and film audiences living in the many countries of the region. Paradoxes in Latin American culture have been the object of study in several fields and Latin American scholars continue to wrestle with the question: "What is Latin America?" The attempted answers invariably foreground the notion that the image of a homogenous Latin America is not only one of many legacies left by colonialism but also that this representation continues to be reinforced by neo-colonial structures. Indeed, the paradoxical character of Latin American culture, where languages, historical processes and systems of knowledge are not always commensurable with each other, is understood as the direct effect of centuries-old, ongoing and overlapping histories of colonialism, capitalist imperialism, social revolution, dictatorship and exile. Cinema, of course, has not been immune to, but on the contrary intervened, these historical circumstances. Thus, with an innate tendency towards homogenisation, stereotyping and exoticism," Latin American cinema" is at its best a category of analysis in Cinema Studies in English. At its worst, it's a marketing label used by both international publishers of cinema books and festival film distributors.